Conductive paste for solar cell, preparation method of conductive paste and electrode

By using carbon-based nano-copper particles and conductive paste with optimized components, the problem of easy oxidation of conductive paste of solar cells in high-temperature aerobic environment is solved, which achieves cost reduction and performance improvement, forms a stable conductive network, extends battery life and improves conversion efficiency.

CN120727341APending Publication Date: 2025-09-30HUAIAN JIETAI NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511127345.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Existing conductive pastes for solar cells have problems such as easy oxidation of copper, high cost, and unstable battery performance, especially in high-temperature oxygen environments, which affects the battery life and conversion efficiency.

Method used

Carbon-based nano-copper particles are used as the conductive phase, combined with an appropriate amount of glass powder and organic additives, and a conductive paste is formed through a specific preparation method and process, including particle size control of carbon-based nano-copper particles and optimization of the ratio of glass powder and organic additives, to ensure that copper oxidation is inhibited during high-temperature sintering and to improve adhesion and conductivity.

Benefits of technology

It effectively prevents copper oxidation, reduces costs, improves battery performance and life, forms good ohmic contact, and enhances the market competitiveness and conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120727341A_ABST
    Figure CN120727341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, and particularly discloses conductive paste for a solar cell, a preparation method of the conductive paste and an electrode. The conductive paste for the solar cell comprises the following components in percentage by weight: 88%-92% of carbon-based nano-copper particles, 4%-6% of glass powder and 4%-6% of an organic additive, the carbon-based nano-copper particles are prepared by reacting copper chloride with glucose and then calcining, the particle size is 52-100nm, and copper oxidation is inhibited by using a carbon layer; the organic additive is composed of a stabilizer, resin and an organic solvent according to a ratio of 1: 3: 9. The conductive material is prepared by mixing, dispersing, grinding and filtering, and can be prepared into a solar cell conductive material by silk-screen printing and high-temperature sintering. The conductive paste is low in cost, high in oxidation resistance and excellent in conductivity, and can replace silver paste to reduce the manufacturing cost of the solar cell, improve the performance and prolong the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a conductive paste for solar cells, a preparation method thereof, and an electrode. Background Art

[0002] Conductive paste is an essential key material in the development and production of solar cells, LTCC components, and integrated modules. Conductive paste primarily consists of a conductive phase, a binder phase (glass phase), and an organic vehicle. These three components are mixed evenly to form a paste with moderate viscosity. This paste is then sintered or cured on a substrate through processes such as screen printing, leveling, drying, and sintering to form a conductive film.

[0003] Currently, silver is the most conductive metal, and silver paste is the mainstream paste used in solar cell manufacturing. Solar cell manufacturing typically involves screen printing or laser transfer of silver paste onto the surface of silicon wafers, followed by high-temperature sintering to form an ohmic contact. However, the high cost of silver paste significantly increases the manufacturing cost of solar cells. With intensified competition in the photovoltaic industry and low product prices, there is an urgent need to find a cheaper conductive paste to replace silver paste without compromising the electrical performance of solar cells.

[0004] Copper metal has excellent high-frequency characteristics, electrical conductivity, solderability and low cost, but copper is easily oxidized in the air, especially in high-temperature oxygen environments, where oxidation is particularly obvious and resistance increases sharply, affecting its application. Currently, existing technologies use copper as a metal electrode, such as copper electroplating, silver-clad copper, etc. to reduce slurry costs. However, these technologies have obvious shortcomings: the thermal expansion coefficients of copper and silicon are quite different, and cracks are easily generated during the sintering process, affecting battery performance; copper electroplating requires a large amount of equipment cost, which increases the production burden; silver-clad copper has problems with uneven silver coating and high contact resistance, and it has not yet completely gotten rid of its dependence on silver, resulting in limited cost reduction.

[0005] Furthermore, existing copper paste technology, while nano-copper powders offer good conductivity, have a large specific surface area and are more susceptible to oxidation at high temperatures. This makes it difficult to inhibit copper oxidation during the sintering process, resulting in poor copper paste oxidation resistance and hindering its application in solar cells. For example, the nano-copper powder (≤50nm) used in patent document CN107622809A lacks carbon-based protection and exhibits severe oxidation during high-temperature sintering.

[0006] Therefore, developing a conductive paste that can effectively prevent oxidation and ensure battery performance has become a technical problem that needs to be urgently solved in the industry. Summary of the Invention

[0007] The present application is to address the above-mentioned problems and provide a conductive paste for solar cells, a preparation method thereof, and an electrode, which can effectively prevent the paste from being oxidized during long-term use, which would cause the battery performance to deteriorate when used as a battery paste, thereby limiting the lifespan and conversion efficiency of solar cells.

[0008] This application is implemented through the following technical solutions:

[0009] The present application provides a conductive paste for solar cells, which comprises the following components by weight percentage:

[0010] Carbon-based nano-copper particles 88%~92%;

[0011] Glass powder 4%~6%;

[0012] Organic additives 4%~6%;

[0013] Wherein, the particle size of the carbon-based nano-copper particles is 52nm~100nm.

[0014] Furthermore, the preparation method of the carbon-based nano-copper particles includes:

[0015] Step (1): reacting a mixed solution of copper chloride and glucose at 90°C to 110°C for 12 to 36 hours; regulating the particle size of carbon-based nano-copper particles by the mass ratio of copper chloride to glucose, wherein the particle size of the carbon-based nano-copper particles is: Y=50.314In(x)+19.028, wherein X is the mass ratio of copper chloride to glucose.

[0016] Step (2): calcining the product of step (1) at a high temperature under the protection of an inert gas at 600° C. to 800° C. for 3 to 9 hours to obtain the carbon-based nano-copper particles.

[0017] Furthermore, the mass ratio of the copper chloride to glucose is 1:0.203~0.513.

[0018] Furthermore, the particle size of the glass powder is 1.5 μm to 3 μm; the glass powder comprises, by mass percentage, 40 to 60% Bi2O3, 20 to 30% B2O3, 10 to 20% SiO2, 0 to 5% Al2O3, and 0 to 5% CaO.

[0019] Furthermore, the organic additive mainly consists of a stabilizer, a resin, and an organic solvent, and the mass ratio of the stabilizer: the resin: the organic solvent is 1:3:9.

[0020] Furthermore, the preparation method of the organic additive includes: mixing a stabilizer, a resin, and an organic solvent in proportion, stirring at 1000 r / min to 3000 r / min for 5 to 6 hours, and filtering and removing impurities with a 300 to 400 mesh polyester net.

[0021] Furthermore, the resin is an epoxy resin; the organic solvent is any one of acetone, isopropyl alcohol, and butyl acetate; and the stabilizer is any one of an organic acid, a surfactant, and a polymer. The organic acid may be formic acid, acetic acid, propionic acid, etc.; the surfactant may be an aliphatic amine curing agent, a polyamide curing agent, an aromatic amine curing agent, an alicyclic amine curing agent, a polyetheramine curing agent, etc. Preferably, the surfactant is an aliphatic amine curing agent.

[0022] Furthermore, the solar cell is any one of a PERC cell, a TOPCon cell and a HJT cell.

[0023] The present application also provides a method for preparing the above-mentioned conductive paste for solar cells, comprising the following steps:

[0024] S1: carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion, and centrifuged and dispersed at 1000 rpm to 3000 rpm for 15 min to 30 min to prepare a mixed slurry;

[0025] S2: The mixed slurry is placed on a three-roll mill for grinding at a roller speed of 70-90 r / min, an organic solvent is added to adjust the viscosity to 60-80 Pa•s, and the conductive slurry is obtained after filtering through a 300-mesh stainless steel mesh.

[0026] The present application also provides a solar cell electrode, which is made by screen printing the above-mentioned conductive paste and then sintering it at 800-1100°C.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present application adopts carbon-based nano-copper particles as the conductive phase of the conductive paste. The carbon layer can reduce copper oxide during high-temperature sintering, effectively inhibiting the oxidation of copper, solving the problem of copper being easily oxidized in a high-temperature oxygen environment, and ensuring the stability of the conductive performance of the conductive paste. Compared with silver paste, the conductive paste of the present application uses copper as the main conductive phase, and the cost of raw materials is greatly reduced. At the same time, the preparation process is relatively simple, which is conducive to reducing the overall manufacturing cost of solar cells and improving the market competitiveness of products. It can replace traditional silver paste in the preparation of solar cell electrodes, and can form good ohmic contact after screen printing and high-temperature sintering, thereby improving the performance and life of solar cells, and has broad application prospects.

[0029] (2) This application balances conductivity and antioxidant properties by optimizing the particle size (52~100nm) of carbon-based nano-copper particles and the proportion of each component. At the same time, the reasonable selection and proportion of glass powder and organic additives ensure the printing performance of copper paste, adhesion after sintering and density, so that the prepared solar cell electrodes have good electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments described in the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0031] Figure 1 This is a microscopic morphology (SEM) image of the carbon-based nano-copper particles provided in Example 1 of the present application;

[0032] Figure 2 This is a microscopic morphology (TEM) image of the carbon-based nano-copper particles provided in Example 1 of the present application; DETAILED DESCRIPTION

[0033] In the following description, numerous specific details are set forth to provide a thorough understanding of the present invention. However, it will be apparent to one of ordinary skill in the art that these specific details are not necessarily required to practice the present invention. In other embodiments, well-known materials or methods are not specifically described to avoid obscuring the present invention.

[0034] Throughout this specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in connection with the embodiment or example is included in at least one embodiment of the present invention. Thus, appearances of the phrases "one embodiment," "an embodiment," "an example," or "an example" in various places throughout this specification are not necessarily all referring to the same embodiment or example. Furthermore, the particular features, structures, or characteristics may be combined in any suitable combinations and / or subcombinations in one or more embodiments or examples. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0035] In a first aspect, the present application provides a conductive paste for solar cells, comprising the following components by weight percentage:

[0036] Carbon-based nano-copper particles 88%~92%;

[0037] Glass powder 4%~6%;

[0038] Organic additives 4%~6%;

[0039] Among them, the particle size of carbon-based nano-copper particles is 52nm~100nm.

[0040] Carbon-based nano-copper particle content: dominates the conductivity (resistivity) after sintering; the higher the content, the better the conductivity, but too high a content will damage printability, film density and adhesion.

[0041] Glass powder content: dominates the adhesion to the substrate and solder resistance after sintering, and also affects the conductivity (excessive amount will block the conductive path) and film density; it needs to match the thermal expansion coefficient of the substrate.

[0042] Organic additive content: It determines the rheological properties (viscosity, thixotropy), printing / coating performance, dry film thickness and solid content of the slurry. Too little organic additive will lead to the slurry being too thick, difficult to disperse and having poor printability. Too much organic additive will result in low solid content, thin dry film and loose film layer after sintering.

[0043] In a specific embodiment, the preparation method of carbon-based nano-copper particles includes:

[0044] Step (1): reacting a mixed solution of copper chloride and glucose at 90°C to 110°C for 12 to 36 hours; regulating the particle size of the carbon-based nano-copper particles by the mass ratio of copper chloride to glucose, the particle size of the carbon-based nano-copper particles being: Y=50.314In(x)+19.028, wherein X is the mass ratio of copper chloride to glucose.

[0045] Step (2): calcining the product of step (1) at a high temperature under the protection of an inert gas at 600° C. to 800° C. for 3 to 9 hours to obtain carbon-based nano-copper particles.

[0046] The microscopic morphology of carbon-based nano-copper particles (nano-copper Cu-NPs@C loaded on carbon spheres) is as follows: Figure 1-2 As shown, using carbon-based nano-copper particles as the conductive phase material of the conductive paste has the following advantages:

[0047] 1. Carbon-based nano-copper particles have a large specific surface area and excellent conductivity, which can significantly improve the conductivity of copper paste, ensuring good ohmic contact between the electrodes of solar cells, thereby reducing resistance loss;

[0048] 2. Carbon-based nano-copper particles are small in size and have many active sites, which can accelerate the reaction rate in the subsequent conductive paste preparation process and increase the reaction degree, making the paste more uniform and stable;

[0049] 3. Carbon-based nano-copper particles are easier to melt and dissolve during high-temperature sintering, forming a dense copper phase structure, thereby improving the mechanical strength and adhesion of the conductive paste and reducing cracks generated during the sintering process;

[0050] 4. The size and dispersibility of carbon-based nano-copper particles directly affect the rheological properties of the copper paste, making it more suitable for screen printing or coating processes, ensuring the fineness and uniformity of printed lines;

[0051] 5. The preparation process of carbon-based nano-copper particles is relatively mature, which can effectively reduce the production cost of traditional conductive pastes. At the same time, its high-performance characteristics can replace expensive silver pastes, further reducing the manufacturing cost of solar cells.

[0052] 6. Through carbon-based protection and nano-size effect, copper paste can maintain stable performance during long-term use, reduce performance degradation caused by oxidation or agglomeration, and extend the service life of solar cells.

[0053] In a specific embodiment, the mass ratio of copper chloride to glucose is 1:0.203~0.513.

[0054] The initial mass ratio of copper chloride to glucose in this application seeks a balance between conductivity, adhesion / reliability, and printability / processability. It not only has a highly conductive thick film circuit and a high-adhesion electrode, but also has good rheological properties for fine line printing.

[0055] In one specific embodiment, the glass powder has a particle size of 1.5 μm to 3 μm. The glass powder comprises, by mass percentage, the following: Bi2O3 40-60%, B2O3 20-30%, SiO2 10-20%, Al2O3 0-5%, and CaO 0-5%. A coarse glass powder particle size may affect dispersibility, while a finer particle size may increase sintering activity. The glass powder primarily utilizes a lead-free glass powder system. Bi2O3 (40-60%) lowers the melting point and improves fluidity; B2O3 (20-30%) acts as a glass network former, regulating viscosity and sintering activity; SiO2 (10-20%) enhances chemical stability and mechanical strength; and other components (Al2O3 (0-5%), CaO (0-5%)) fine-tune the thermal expansion coefficient or corrosion resistance. The lead-free glass powder system and carbon-based nano-copper particles have a synergistic effect, forming a stable glass network during sintering and reducing heavy metal seepage; breaking through the limitation of traditional copper paste that requires the addition of lead glass to improve fluidity, and complying with environmental regulations such as RoHS.

[0056] In a specific embodiment, the organic additive mainly consists of a stabilizer, a resin, and an organic solvent, and the mass ratio of stabilizer:resin:organic solvent is 1:3:9.

[0057] In a specific embodiment, the preparation method of the organic additive includes: mixing a stabilizer, a resin, and an organic solvent in proportion, stirring at 1000 r / min to 3000 r / min for 5 to 6 hours, and filtering through a 300-400 mesh polyester net to remove impurities.

[0058] In a specific embodiment, the resin is an epoxy resin; the organic solvent is any one of acetone, isopropyl alcohol, and butyl acetate; and the stabilizer is any one of an organic acid, a surfactant, and a polymer. The organic acid may be formic acid, acetic acid, propionic acid, or the like; and the surfactant may be an aliphatic amine curing agent, a polyamide curing agent, an aromatic amine curing agent, an alicyclic amine curing agent, or a polyetheramine curing agent, preferably an aliphatic amine curing agent.

[0059] The solar cell is any one of a PERC cell, a TOPCon cell and a HJT cell.

[0060] In a second aspect, the present application further provides a method for preparing the above-mentioned conductive paste for solar cells, comprising the following steps:

[0061] S1: carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion, and centrifuged and dispersed at 1000 rpm to 3000 rpm for 15 min to 30 min to prepare a mixed slurry;

[0062] S2: The mixed slurry is placed on a three-roll mill for grinding at a roller speed of 70-90 r / min, an organic solvent is added to adjust the viscosity to 60-80 Pa•s, and the conductive slurry is obtained after filtering through a 300-mesh stainless steel mesh.

[0063] In a third aspect, the present application further provides a solar cell electrode, which is made by screen printing the above-mentioned conductive paste and then sintering it at 800-1100°C.

[0064] The following will clearly and completely describe the technical solutions of the present invention in conjunction with specific embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0065] Example 1

[0066] This embodiment provides a conductive paste for solar cells, the components of which are as follows by weight: 92% carbon-based nano-copper particles, 4% glass powder, and 4% organic additives; the mass ratio of copper chloride to glucose is 1:0.203, and the particle size of the carbon-based nano-copper particles is 100 nm.

[0067] The preparation method is as follows:

[0068] 1. Preparation of carbon-based copper nanoparticles:

[0069] Step (1): copper chloride and glucose were mixed in a mass ratio of 1:0.203 and reacted at 110°C for 24 hours;

[0070] Step (2): The black solid product of step (1) was calcined at 700°C in a quartz tube furnace at an argon flow rate of 20 mL / min for 6 hours, and then cooled to room temperature. Subsequently, the solid sample was fully ground in an agate mortar, washed and dried to obtain carbon-based nano-copper particles with a particle size of 100 nm.

[0071] The above preparation method obtains nano-copper supported on carbon balls (i.e., carbon-based nano-copper particles). At this time, the nano-copper is small in size, has a larger specific surface area, and has more active sites, which can accelerate the reaction rate in the subsequent conductive paste preparation process and improve the reaction degree, making the conductive paste more uniform and stable. The microscopic morphology of the carbon-based nano-copper particles is as follows: Figure 1-2 As shown; the overall distribution of carbon-based nano-copper particles can be clearly observed from the figure. The particles are dispersed relatively evenly, showing a certain agglomeration phenomenon but the degree is relatively light, which is conducive to the subsequent good conductive effect in the conductive paste.

[0072] 2. Preparation of glass powder: Weigh Bi2O according to mass percentage 40%, B2O3 30%, SiO2 20%, Al2O3 5%, CaO5%, mix and grind to a particle size of 1.5μm.

[0073] 3. Preparation of organic additives:

[0074] Weigh aliphatic amine curing agent (stabilizer), epoxy resin (resin), and acetone (organic solvent) according to the weight percentage of stabilizer: resin: organic solvent = 1:3:9;

[0075] The above raw materials were mixed and dissolved in each other by stirring at a stirring speed of 1000 r / min for 6 hours until the epoxy resin was completely dissolved in the organic solvent, and then filtered through a 400-mesh polyester net to remove impurities to obtain the organic additive.

[0076] 4. Preparation of conductive paste:

[0077] S1: The carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion and added to a high-speed centrifuge at a dispersion speed of 1000 r / min for 30 min until the dispersion is uniform and there is no powdery particle feeling, thereby preparing a mixed slurry;

[0078] S2: Add the above-mentioned materials to a three-roll mill, adjust the roller speed of the three-roll mill to 70 r / min, control the pressure value to 3±0.5 MPa, and roll the mill 5 times to achieve a fully grinding effect. Fine-tune the slurry viscosity by adding an appropriate amount of organic solvent to make the slurry viscosity 60 Pa·s, and then filter it with a 300-mesh stainless steel mesh to obtain a conductive slurry for solar cell slurry printing.

[0079] Example 2

[0080] This embodiment provides a conductive paste for solar cells, the components of which are as follows by weight: 90% carbon-based nano-copper particles, 5% glass powder, and 5% organic additives; the mass ratio of copper chloride to glucose is 1:0.289, and the particle size of the carbon-based nano-copper particles is 80 nm.

[0081] The preparation method is as follows:

[0082] 1. Preparation of carbon-based copper nanoparticles:

[0083] Step (1): copper chloride and glucose were mixed in a mass ratio of 1:0.289 and reacted at 90°C for 36 hours;

[0084] Step (2): The black solid product of step (1) was calcined at 600°C in a quartz tube furnace for 3 hours at an argon flow rate of 20 mL / min, and then cooled to room temperature. Subsequently, the solid sample was fully ground in an agate mortar, washed and dried to obtain carbon-based nano-copper particles with a particle size of 80 nm.

[0085] 2. Preparation of glass powder: Weigh Bi2O according to mass percentage 58%, B2O3 20%, SiO2 20%, Al2O3 1%, CaO1%, mix and grind to a particle size of 3μm.

[0086] 3. Preparation of organic additives:

[0087] Weigh aliphatic amine curing agent (stabilizer), epoxy resin (resin), and acetone (organic solvent) according to the weight percentage of stabilizer: resin: organic solvent = 1:3:9;

[0088] The above raw materials were mixed and dissolved in each other by stirring at a stirring speed of 3000 r / min for 5 hours until the epoxy resin was completely dissolved in the organic solvent. The mixture was then filtered through a 300-mesh polyester net to remove impurities, thereby obtaining an organic additive.

[0089] 4. Preparation of conductive paste:

[0090] S1: The carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion and added to a high-speed centrifuge at a dispersion speed of 3000 r / min for 15 minutes until the dispersion is uniform and there is no powdery particle feeling, thereby preparing a mixed slurry;

[0091] S2: Add the above-mentioned materials to a three-roll mill, adjust the roller speed of the three-roll mill to 90 r / min, control the pressure value to 3±0.5 MPa, and roll the mill 5 times to achieve a sufficient grinding effect. Fine-tune the slurry viscosity by adding an appropriate amount of organic solvent to make the slurry viscosity 80 Pa·s, and then filter it with a 300-mesh stainless steel mesh to obtain a conductive slurry for solar cell slurry printing.

[0092] Example 3

[0093] This embodiment provides a conductive paste for solar cells, the components of which are as follows by weight: 88% carbon-based nano-copper particles, 6% glass powder, and 6% organic additives; the mass ratio of copper chloride to glucose is 1:0.455, and the particle size of the carbon-based nano-copper particles is 60 nm.

[0094] The preparation method is as follows:

[0095] 1. Preparation of carbon-based copper nanoparticles:

[0096] Step (1): copper chloride and glucose were mixed in a mass ratio of 1:0.455, and reacted at 100°C for 24 hours;

[0097] Step (2): The black solid product of step (1) was calcined at 800°C in a quartz tube furnace for 3 hours at an argon flow rate of 20 mL / min, and then cooled to room temperature. Subsequently, the solid sample was fully ground in an agate mortar, washed and dried to obtain carbon-based nano-copper particles with a particle size of 60 nm.

[0098] 2. Preparation of glass powder: Weigh Bi2O according to mass percentage 60%, B2O3 20%, SiO2 10%, Al2O3 5%, CaO5%, mix and grind to a particle size of 2μm.

[0099] 3. Preparation of organic additives:

[0100] Weigh aliphatic amine curing agent (stabilizer), epoxy resin (resin), and acetone (organic solvent) in a weight ratio of stabilizer: resin: organic solvent = 1:3:9;

[0101] The above raw materials were mixed and dissolved in each other by stirring at a stirring speed of 2000 r / min for 5.5 hours until the epoxy resin was completely dissolved in the organic solvent. The mixture was then filtered through a 400-mesh polyester net to remove impurities, thereby obtaining an organic additive.

[0102] 4. Preparation of conductive paste:

[0103] S1: The carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion and added to a high-speed centrifuge at a dispersion speed of 2000 r / min for 25 minutes until the dispersion is uniform and there is no powdery particle feeling, thereby preparing a mixed slurry;

[0104] S2: Add the above-mentioned materials to a three-roll mill, adjust the roller speed of the three-roll mill to 80 r / min, control the pressure value to 3±0.5 MPa, and roll the mill 5 times to achieve a sufficient grinding effect. Fine-tune the slurry viscosity by adding an appropriate amount of organic solvent to make the slurry viscosity 70 Pa·s, and then filter it with a 300-mesh stainless steel mesh to obtain a conductive slurry for solar cell slurry printing.

[0105] Example 4

[0106] This embodiment provides a conductive paste for solar cells, the components of which are as follows by weight: 92% carbon-based nano-copper particles, 4% glass powder, and 4% organic additives; the mass ratio of copper chloride to glucose is 1:0.513, and the particle size of the carbon-based nano-copper particles is 52 nm.

[0107] The preparation method is as follows:

[0108] 1. Preparation of carbon-based copper nanoparticles:

[0109] Step (1): copper chloride and glucose were mixed in a mass ratio of 1:0.513, and reacted at 110°C for 24 hours;

[0110] Step (2): The black solid product of step (1) was calcined at 700°C in a quartz tube furnace at an argon flow rate of 20 mL / min for 6 hours, and then cooled to room temperature. Subsequently, the solid sample was fully ground in an agate mortar, washed and dried to obtain carbon-based nano-copper particles with a particle size of 52 nm.

[0111] 2. Preparation of glass powder: Weigh Bi2O according to mass percentage 40%, B2O3 30%, SiO2 20%, Al2O3 5%, CaO5%, mix and grind to a particle size of 1.5μm.

[0112] 3. Preparation of organic additives:

[0113] Weigh aliphatic amine curing agent (stabilizer), epoxy resin (resin), and acetone (organic solvent) according to the weight percentage of stabilizer: resin: organic solvent = 1:3:9;

[0114] The above raw materials were mixed and dissolved in each other by stirring at a stirring speed of 1000 r / min for 6 hours until the epoxy resin was completely dissolved in the organic solvent. The mixture was then filtered through a 400-mesh polyester mesh to remove impurities, thereby obtaining an organic additive.

[0115] 4. Preparation of conductive paste:

[0116] S1: The carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion and added to a high-speed centrifuge at a dispersion speed of 1000 r / min for 30 min until the dispersion is uniform and there is no powdery particle feeling, thereby preparing a mixed slurry;

[0117] S2: Add the above-mentioned materials to a three-roll mill, adjust the roller speed of the three-roll mill to 70 r / min, control the pressure value to 3±0.5 MPa, and roll the mill 5 times to achieve a fully grinding effect. Fine-tune the slurry viscosity by adding an appropriate amount of organic solvent to make the slurry viscosity 60 Pa·s, and then filter it with a 300-mesh stainless steel mesh to obtain a conductive slurry for solar cell slurry printing.

[0118] Example 5

[0119] This embodiment provides a conductive paste for solar cells. Compared with Example 1, glass powder with a particle size of 1.4 μm is used; the remaining components and preparation steps are the same.

[0120] Example 6

[0121] This embodiment provides a conductive paste for solar cells. Compared with Example 1, glass powder with a particle size of 3.1 μm is used; the remaining components and preparation steps are the same.

[0122] Comparative Example 1

[0123] This comparative example provides a conductive paste. Compared with Example 4, nano copper powder with a particle size of 52 nm (without carbon-based coating) is used to replace the carbon-based nano copper particles; the remaining components and preparation steps are the same.

[0124] Comparative Example 2

[0125] This comparative example provides a conductive paste for solar cells. Compared with Example 4, the particle size of the carbon-based nano-copper particles is 50 nm (obtained by adjusting the mass ratio of copper chloride to glucose); the remaining components and preparation steps are the same.

[0126] Comparative Example 3

[0127] This comparative example provides a conductive paste for solar cells. Compared with Example 1, the particle size of the carbon-based nano-copper particles is 102 nm (obtained by adjusting the mass ratio of copper chloride to glucose); the remaining components and preparation steps are the same.

[0128] Comparative Example 4

[0129] This comparative example provides a conductive paste for solar cells. Compared with Example 1, the content of carbon-based nano-copper particles exceeds the standard: glass powder 4%, carbon-based nano-copper particles 93%, and carrier 3%; the remaining components and preparation steps are the same.

[0130] Comparative Example 5

[0131] This comparative example provides a conductive paste for solar cells. Compared with Example 1, the glass powder content exceeds the standard: glass powder 8%, carbon-based nano-copper particles 88%, and carrier 4%; the remaining components and preparation steps are the same.

[0132] Performance Testing

[0133] The conductive pastes for solar cells prepared in Examples 1-6 and Comparative Examples 1-5 were screen-printed onto the surface of silicon wafers for PERC / TOPCon / HJT cells and sintered at 800-1100°C under inert gas protection to form electrodes. The following properties were tested: 1. Resistivity: measured by the four-probe method; 2. Oxidation resistance: after 1000 hours in air at 150°C, the resistivity change rate was tested (≤5% was excellent); 3. Adhesion: tested by the cross-hatch method (ASTM D3359); 4. Conversion efficiency: the conversion efficiency of the complete cell was tested under standard light intensity (1000 W / m²); 5. Solderability: the solder wetting angle was tested (≤30° was good). The test data are shown in Table 1.

[0134] Table 1 Test results of batteries of Examples and Comparative Examples

[0135]

[0136] Performance test data conclusion analysis:

[0137] 1. Example effect analysis:

[0138] The resistivity of Examples 1-4 is relatively low, all below 6. This is due to the use of carbon-based nano-copper particles as the conductive phase. The carbon-based nano-copper particle content ranges from 88% to 92%, ensuring excellent conductivity. Furthermore, the carbon layer reduces copper oxide during high-temperature sintering, effectively inhibiting copper oxidation and achieving excellent oxidation resistance.

[0139] The adhesion is between 7.9-8.7 N / cm, which is a good performance. This is due to the glass powder content being controlled at 4%-6%, which has a high match with the thermal expansion coefficient of the substrate and ensures good adhesion to the substrate after sintering.

[0140] The conversion efficiency is at a relatively high level of 25.6%-26.0%, and the solderability is good, indicating that the proportions of the components are reasonably optimized. The addition of organic additives gives the slurry good printing and sintering properties, enabling the formation of a dense conductive film layer, thus ensuring the efficient operation of the solar cell.

[0141] The glass powder particle size of Example 5 is too fine, which increases the sintering activity of the slurry, resulting in excessive sintering and a decrease in adhesion to 7.0 N / cm; while the glass powder particle size of Example 6 is too coarse, which affects the dispersibility of the slurry, resulting in poor dispersibility, increased resistivity and wetting angle; therefore, the conversion efficiency performance of Examples 5 and 6 is worse than that of Examples 1-4.

[0142] In summary, the embodiments achieve the characteristics of low cost, strong antioxidant properties, and excellent conductivity of the conductive paste by controlling the particle size of carbon-based nano-copper particles (52-100nm), the proportion of each component (88%-92% carbon-based nano-copper particles, 4%-6% glass powder, and 4%-6% organic additives), and the preparation process parameters. This can replace silver paste to reduce battery manufacturing costs and improve performance and life.

[0143] 2. Comparative effect analysis:

[0144] Comparative Example 1 uses nano copper powder without carbon coating, and the resistivity is as high as 15.6 , poor oxidation resistance. This is because without the protection of the carbon layer, the nano copper powder is easily oxidized at high temperatures, resulting in a sharp drop in conductivity, which in turn reduces the conversion efficiency to as low as 23.33% and poor solderability.

[0145] The particle size of the carbon-based nano-copper particles in Comparative Example 2 is 50 nm, which is smaller than the range of 52-100 nm defined in this application, and the resistivity is 7.5 , the oxidation resistance is only good. Due to the small particle size, it is still easy to oxidize at high temperature, which affects the conductivity and oxidation resistance, and the adhesion and conversion efficiency are not as good as those of the embodiment.

[0146] The particle size of the carbon-based nano-copper particles in Comparative Example 3 is 102 nm, which is larger than the range specified in this application, and the resistivity is 8.2 The larger particle size reduces the contact area between particles, which reduces the conductivity. It also affects the dispersion of the slurry and the density after sintering, resulting in unsatisfactory adhesion and conversion efficiency.

[0147] This application balances cost and performance through precise control of the copper chloride-glucose mass ratio: when the particle size is >100nm, the cost is lower, but the activity decreases; when the particle size is <52nm, the antioxidant property is poor and higher cost protection is required; this application provides an "optimal cost-effective range" (52-100nm), which not only meets the conductivity requirements but also avoids the excessively high preparation cost of nanomaterials.

[0148] In Comparative Example 4, the carbon-based nano-copper particle content was 93%, exceeding the range of 88%-92%. This resulted in poor printability, insufficient film density, and adhesion of 5.5 N / cm. While conductivity was slightly improved, overall performance was inferior to that of the examples. Therefore, a higher carbon-based nano-copper particle content in a conductive paste does not necessarily mean better performance. This application provides an optimal range for the content of carbon-based nano-copper particles.

[0149] In Comparative Example 5, the glass powder content is 8%, which is beyond the range of 4%-6%, and the resistivity is 9.4 , and the oxidation resistance is medium. Excessive glass powder blocks the conductive path, reduces the conductivity, and also affects the density of the film layer, resulting in reduced adhesion, lower conversion efficiency, and poor solderability.

[0150] This application uses carbon-based nano-copper particles as the conductive phase of the conductive paste. During the high-temperature sintering process (800-1100°C) of the carbon-based nano-copper particles, the carbon layer not only inhibits copper oxidation, but also reduces the oxidized CuO to Cu, forming a dynamic "self-repair" mechanism; even if local copper particles are oxidized due to process fluctuations, the carbon layer can reduce them to ensure the integrity of the conductive network and avoid the performance degradation of traditional copper paste due to oxidation; traditional copper paste or silver-clad copper as the conductive phase of the conductive paste is irreversible once oxidized, but this application achieves long-term stability by using carbon-based nano-copper particles for protection.

[0151] Carbon-based nano-copper particles have a high specific surface area and active sites, which enhance interfacial bonding with glass powder and resin. After sintering, they form a denser conductive film, reduce sintering cracks, and improve electrode adhesion to the silicon substrate, further reducing contact resistance. Experimental Example 1 shows that carbon-based nano-copper particles maintain high adhesion at a concentration of 92%, while conventional copper pastes are prone to delamination at concentrations greater than 90%.

[0152] In addition, the size effect of carbon-based nano-copper particles (52-100nm) reduces the sintering activation energy, allowing densification at relatively low temperatures (such as 750-850°C); it is compatible with temperature-sensitive substrates (such as flexible photovoltaic modules); and it reduces the damage of high temperatures to the passivation layer of silicon wafers, thereby improving battery efficiency (such as the passivation layer of PERC / TOPCon batteries is sensitive to high temperatures).

[0153] The uniform dispersion of carbon-based nano-copper particles (inhibiting agglomeration through carbon loading) makes the viscosity of the conductive paste easier to control, adapting to high-precision printing (such as fine grid lines <20μm): achieving printing resolution similar to that of silver paste, breaking through the rough line problem caused by coarse particles in traditional copper paste; reducing printing defects (such as broken grids and edge burrs), and improving the photoelectric conversion efficiency of batteries.

[0154] In summary, this application adopts carbon-based nano-copper particles, optimizes the proportion of each component and the preparation process, so that the conductive paste has the advantages of low cost, strong oxidation resistance, and excellent conductivity. It can replace silver paste to reduce the manufacturing cost of solar cells and improve battery performance and life.

[0155] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in this field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A conductive paste for solar cells, characterized in that: The following components are included by weight percentage: Carbon-based nano-copper particles 88%~92%; Glass powder 4%~6%; Organic additives 4%~6%; Wherein, the particle size of the carbon-based nano-copper particles is 52nm~100nm.

2. The conductive paste for solar cells according to claim 1, wherein The preparation method of the carbon-based nano-copper particles comprises: Step (1): reacting a mixed solution of copper chloride and glucose at 90°C to 110°C for 12 to 36 hours; regulating the particle size of the carbon-based nano-copper particles by the mass ratio of copper chloride to glucose, wherein the particle size of the carbon-based nano-copper particles is: Y=50.314In(x)+19.028, wherein X is the mass ratio of copper chloride to glucose; Step (2): calcining the product of step (1) at a high temperature under the protection of an inert gas at 600° C. to 800° C. for 3 to 9 hours to obtain the carbon-based nano-copper particles.

3. The conductive paste for solar cells according to claim 2, wherein: The mass ratio of the copper chloride to glucose is 1:0.203~0.

513.

4. The conductive paste for solar cells according to claim 1, wherein The particle size of the glass powder is 1.5 μm to 3 μm; the glass powder comprises, by mass percentage, 40 to 60% Bi2O3, 20 to 30% B2O3, 10 to 20% SiO2, 0 to 5% Al2O3, and 0 to 5% CaO.

5. The conductive paste for solar cells according to claim 1, wherein The organic additive consists of a stabilizer, a resin, and an organic solvent, and the mass ratio of the stabilizer: the resin: the organic solvent is 1:3:

9.

6. The conductive paste for solar cells according to claim 5, wherein: The preparation method of the organic additive comprises: mixing a stabilizer, a resin and an organic solvent in proportion, stirring at 1000 r / min to 3000 r / min for 5 to 6 hours, and filtering and removing impurities with a 300-400 mesh polyester net.

7. The conductive paste for solar cells according to claim 5, wherein: The resin is epoxy resin; the organic solvent is any one of acetone, isopropyl alcohol, and butyl acetate; and the stabilizer is any one of organic acid, surfactant, and polymer.

8. The conductive paste for solar cells according to claim 1, wherein The solar cell is any one of a PERC cell, a TOPCon cell and a HJT cell.

9. The method for preparing a conductive paste for solar cells according to any one of claims 1 to 8, wherein: The steps include: S1: carbon-based nano-copper particles, glass powder, and organic additives are mixed in proportion, and centrifuged and dispersed at 1000 rpm to 3000 rpm for 15 min to 30 min to prepare a mixed slurry; S2: The mixed slurry is placed on a three-roll mill for grinding at a roller speed of 70-90 r / min, an organic solvent is added to adjust the viscosity to 60-80 Pa·s, and the conductive slurry is obtained after filtering through a 300-mesh stainless steel mesh.

10. A solar cell electrode, characterized in that: The conductive paste according to any one of claims 1 to 8 is screen-printed and then sintered at 800-1100° C. to produce a solar cell electrode.

Citation Information

Cited By

  • Solar cell and method of manufacturing the same, stacked cell, and photovoltaic module

    CN122349266A